Students Learning Activeness: An Experimental Study On The Effectiveness Of The Cooperative Learning Model Question Students Have - Nirwana, Nirwana; Azizah, Nurul; Zulhannan, Zulhannan; Romlah, Listiyani Siti; Rahmatika, Zahra (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Students learning activeness can be increased by implementing interactive learning models. This research was motivated by low learning activity. This research aims to determine the effectiveness of implementing the Question Students Have type cooperative learning model on students' learning activity at MTS Nurul Huda Pringsewu, especially in the subject of moral beliefs. This research uses a quantitative approach with a Quasi Experimental Design research type. The sampling technique uses simple random sampling. The results of the normality test for the experimental group where the sig value. 0.234 is greater than 0.05, indicating that the data is normally distributed. Meanwhile in the control group it was 0.391 where the sig value. greater than 0.05. The t test results show data where the sig value. 0.409 which means that the sig value. (2-tailed) greater than 0.05. so it can be concluded that H_0 is accepted and H_1 is rejected. so the results of this research show that the experimentation of the question students have learning model is not significant on students' learning activeness.